A full mouth rehabilitation restoring function and aesthetics (case report) - Muhammad R. Morgan; Ahmed W. Belal; Raneem M. Gamal; Eman M. Soliman (Advances in Medical, Pharmaceutical and Dental Research)
Background: This study presents a clinical case report of a middle-aged patient with pain in the posterior mandibular first molar, especially while eating, multiple edentulous spaces, and bleeding upon brushing. Periodontal therapy, non-surgical extraction, endodontic therapy, restorative treatment, and prosthetic treatment were all included in the multidisciplinary procedure. Purpose: Restoring appropriate occlusion and enhancing appearance were the goals of the treatment plan. Methodology: The patient's treatment approach was commenced by clinical and radiographical examination, including panoramic X-ray and multiple periapical X-rays, followed by diagnosis, phases of treatment, the insertion of monolithic zirconia full coverage restorations, and porcelain fused to metal fixed partial denture. Conclusion: There was an improvement concerning esthetics and function. An integrated treatment strategy is crucial for achieving optimal outcomes in full-mouth rehabilitation. Appropriate treatment planning requires careful assessment of the etiology, history, and factors pertaining to the oral health condition.   Received: 30 August 2024 Accepted:18 September 2024 Published: 19 September 2024